The Effect of Boiling Papaya Leaves on Joint Pain Complaints in Older People with Rheumatoid Arthritis at the Pekkabata Public Healthcare - Normalia, Normalia (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Rheumatoid arthritis is an inflammatory illness characterized by the deterioration of joints and synovial lining, particularly in the hands, feet, and knees. There are both pharmacological and non-pharmacological treatments for rheumatoid arthritis. Decoction of papaya leaves is one of the non-pharmaceutical remedies for rheumatoid arthritis that reduces joint pain complaints. This study aimed to assess the effect of papaya leaf decoction on joint pain complaints in senior patients with rheumatoid arthritis at Pekkabata Health Center. This study utilized a quasi-experiment with a one-group Pre-post-test design technique. Purposive sampling was employed to collect data from a total of 10 individuals. Using the Paired T-Test statistic, the data were evaluated. The findings of the Paired T-Test with a p-value of 0.000 indicate that papaya leaf decoction affects joint pain complaints in older patients with rheumatoid arthritis at the Pekkabata Public Health Center. This study suggests that a papaya leaf decoction can be used as an alternative, non-pharmaceutical treatment for rheumatoid arthritis to help lessen joint pain complaints.